2017
DOI: 10.1016/j.adolescence.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Does prior domain‐specific content knowledge influence students' recall of arguments surrounding interdisciplinary topics?

Abstract: Awareness of various arguments can help interactants present opinions, stress points, and build counterarguments during discussions. At school, some topics are taught in a way that students learn to accumulate knowledge and gather arguments, and later employ them during debates. Prior knowledge may facilitate recalling information on well structured, fact-based topics, but does it facilitate recalling arguments during discussions on complex, interdisciplinary topics? We assessed the prior knowledge in domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…On balance, the literature suggests that content knowledge does play a role in enhancing argumentation about SSI; however, the relationship might be non-linear, meaning that a certain depth of knowledge is required before knowledge shows a positive effect on argumentation. Other studies have investigated the relationship between students' knowledge and the number of their arguments, hypothesising that students with more robust knowledge will produce more arguments (Means & Voss, 1996;Schmidt et al, 2017). Evagorou and Osborne (2013), for example, examined the number of claims in students' collaborative argumentation.…”
Section: The Role Of Issue Familiarity In Argumentationmentioning
confidence: 99%
“…On balance, the literature suggests that content knowledge does play a role in enhancing argumentation about SSI; however, the relationship might be non-linear, meaning that a certain depth of knowledge is required before knowledge shows a positive effect on argumentation. Other studies have investigated the relationship between students' knowledge and the number of their arguments, hypothesising that students with more robust knowledge will produce more arguments (Means & Voss, 1996;Schmidt et al, 2017). Evagorou and Osborne (2013), for example, examined the number of claims in students' collaborative argumentation.…”
Section: The Role Of Issue Familiarity In Argumentationmentioning
confidence: 99%
“…The learning process also needs to be resource rich in terms of students' time and effort; and real-world relevant, for example connected with their future profession and work (Blackmore, 2009). Additionally, there is a strong role of students' prior knowledge and skills, such as known concepts, learning expectations and learning strategies on their academic achievements (Nasir & Hand, 2006;Schmidt, Rothgangel, & Grube, 2017;Schoenfeld, 1999). In science education, maintaining connections and consistency of tasks is an important requirement (Sikorski & Hammer, 2017).…”
Section: Emerging Educational Conceptsmentioning
confidence: 99%
“…To engage the students effectively, it is also important to keep a proper balance of cognitive, behavioural and emotional tasks; for example complex coding, time-demanding assignment, and practical programming design for future professional work. However, for designing suitable tasks, lecturers need to take account of students' level of competency and prior knowledge (see Schmidt et al, 2017;Nasir & Hand, 2006;and Schoenfeld, 1999 in 'Emerging educational concepts' section). In this regard, a pre-course assessment of programming competencies may help lecturers understand the baseline knowledge and skills of their student groups, and also decide appropriate programming tasks for them.…”
Section: Address Pedagogical Issues In Teaching Preparationmentioning
confidence: 99%
“…In a classic developmental study of domain knowledge, informal reasoning, and argumentation, Means and Voss (1996) found that knowledge significantly related to the number and type of reasons generated, but not to the soundness or acceptability of arguments, which were explained by ability track (which were IQ-based). More recently Schmidt, Rothgangel, and Grubec (2017) studied recall of arguments and found that prior domain knowledge helped students recall arguments. Presumably, most educators would hope that their students would be better able to identify and dismiss arguments made on specious grounds.…”
Section: Study 2: Disciplinary Knowledge and The Consequences Of Goodmentioning
confidence: 99%